PanCareLIFE: The scientific basis for a European project to improve long-term care regarding fertility, ototoxicity and health-related quality of life after cancer occurring among children and adolescents. (November 2018) - Byrne, Julianne; Grabow, Desiree; Campbell, Helen; O'Brien, Kylie; Bielack, Stefan; am Zehnhoff-Dinnesen, Antoinette; Calaminus, Gabriele; Kremer, Leontien; Langer, Thorsten; van den Heuvel-Eibrink, Marry M.; van Dulmen-den Broeder, Eline; Baust, Katja; et al.
Abstract: Aims: Survival after cancer diagnosed during childhood or adolescence continues to improve with new treatments and supportive therapies. Optimal long-term care requires that risks to vulnerable organs are clearly defined and translated into guidelines that are implemented into practice. PanCareLIFE is a pan-European consortium that addresses survivorship issues comprising fertility, hearing impairment and quality of life. This article describes the scientific basis of PanCareLIFE's studies. Methods: PanCareLIFE involves 17 partner institutions from eight European countries, with additional 11 data providers from five other countries. Study designs and methods include molecular genetic, cohort and case-control studies, a longitudinal study and an intervention study. Ethics and data protection issues have been taken into account from the beginning. Results: PanCareLIFE will investigate the way that treatment impairs female fertility, by evaluating anti-Müllerian hormone levels and the underlying genetic susceptibility to loss of fertility. For our fertility studies, more than 6000 survivors have completed questionnaires, more than 1500 provided serum samples and more than 400 case-control triads have been identified. Fertility preservation guidelines for boys and girls will be developed. More than 2000 survivors have contributed audiograms for the ototoxicity study. Almost 1000 samples were sent for genetic analysis related to ototoxicity and gonadal reserve. The SF-36 questionnaire will measure quality of life in more than 10, 000 survivors. Conclusions: The large number of subjects enrolled in PanCareLIFE and the detailed information accumulated will allow in-depth evaluation of important outcomes. Fertility preservation guidelines will help patients and their families make informed decisions and contribute to their long-term well-being. Highlights: PanCareLIFE is a large pan-European study on late effects after childhood cancer. Studies of hearing loss, fertility impairment and quality of life are included. Clinical and genetic methods with new guidelines will lead to improved health.